Pathos, Pleasure and the Ethical Life in Aristippus - Urstad, Kristian (Journal of Ancient Philosophy, 2009)
For many of the ancient Greek philosophers, the ethical life was understood to be closely tied up with important notions like rational integrity, self-control, self-sufficiency, and so on. Because of this, feeling or passion (pathos), and in particular, pleasure, was viewed with suspicion. There was a general insistence on drawing up a sharp contrast between a life of virtue on the one hand and one of pleasure on the other. While virtue was regarded as rational and as integral to advancing one’s well-being or happiness and safeguarding one’s autonomy, pleasure was viewed as largely irrational and as something that usually undermines a life of reason, self-control and self-sufficiency. I want to try to show that the hedonist Aristippus of Cyrene, a student and contemporary of Socrates, was unique in not drawing up such a sharp contrast. Aristippus, I argue, might be seen to be challenging the conception of passion and pleasure connected to loss of self-control and hubristic behavior. Not only do I try to show that pleasure according to Aristippus is much more comprehensive or inclusive than it is usually taken to be, but that a certain kind of control and self-possession actually play an important part in his conception of pleasure and in his hedonism as a whole.